Label‐Free Electrochemical Immunoaffinity Sensor Based on Impedimetric Method for Pesticide Detection. Issue 3 (24th January 2013) - Tran, H. V.; Reisberg, S.; Piro, B.; Nguyen, T. D.; Pham, M. C.
Abstract We present a new approach using a conducting polymer to combine immunoaffinity and electrochemical impedance spectroscopy for atrazine detection. The system is based on a competitive complexation between anti‐atrazine antibody and either atrazine present in the analyzed sample or hydroxyatrazine immobilized on the sensor surface. The process allows to detect atrazine at a very low detection limit (0.2 ng L−1) in a true label‐free format (no redox probe added in solution) by following changes in the electrochemical impedance of the sensor.